Building a Characterized Generation: Project-Based Management of the Pancasila Student Profile in Elementary Schools - Fandu Anugrah; Wasliman, Iim; Sauri, R Supyan; Rostini, Deti (Universitas Islam Negeri Walisongo Semarang in collaboration with PD PGMI Indonesia, 2025)
The younger generation needs to possess strong character and uphold the values of Pancasila to face the challenges of globalization, social change, and cultural transformation. This study aims to describe and analyze the management of the Pancasila Student Profile Strengthening Project in enhancing student character at SDN 1 Kepel and SDN 1 Kertaharja, Ciamis Regency. This study employs a descriptive qualitative case study approach. The sample consists of school principals, teachers, and students selected purposively. Data were collected through interviews, observations, document analysis, and literature reviews. Data analysis follows the Miles and Huberman model, which includes data reduction, data display, and conclusion drawing, with validity ensured through triangulation. Results show that effective planning involves forming an implementation team, assessing school readiness, and designing project themes aligned with Pancasila values. Organizing emphasizes task delegation, resource management, and stakeholder coordination. Implementation focuses on project-based learning in real-world contexts, such as teamwork and environmental conservation. Evaluation is conducted formatively and summatively through rubrics, reflections, and portfolios. Challenges include resource limitations, stakeholder understanding, and curriculum integration. Solutions include teacher training, resource optimization, and community collaboration. The structured P5 management model strengthens Pancasila-based character education, enabling schools to adopt and adapt it for more effective and sustainable implementation.